M Application of Canva Media in the Form of Comics to Improve Negotiation Text Writing Skills for Class X Accounting 1 Students SMKN 6 Surabaya - Ovielia, Dilla; Esterina Mesya Dininda; Nono Tri Hariyanto; ARDHIANTI, MIMAS (Universitas Swadaya Gunung Jati, 2025)
Lack of interest in learning students' negotiation texts at SMKN 6 Surabaya due to the limited media taught. The purpose of this study is to describe the application of Canva media in the form of comics to improve the negotiation text writing skills of students of class X Accounting 1 at SMKN 6 Surabaya. Classroom Action Research (PTK) is used in this approach. There are four steps in the PTK cycle, namely 1) planning, 2) implementation, 3) observation, and 4) reflection. The subjects of this study are 36 students of class X Accounting 1. The location of the research was carried out at SMKN 6 Surabaya, which is located on Jl. Margorejo No. 76, Kec. Margorejo, Surabaya. The data collection techniques in this study consisted of 1) student worksheets (LKPD), 2) questionnaires, 3) interviews, 4) documentation, and 5) observation sheets of the learning process. The data analysis technique uses descriptive statistics. Based on the results of the study, the completion rate is 64%, the average student score in the first cycle is 68. In the second cycle, the average score increased to 78 with a completion rate of 91%. With the help of Canva, students can easily generate ideas and create attractive and well-structured negotiation documents. The conclusion of this study is that the use of Canva media can help students compose negotiation texts and become better writers.